Tradisi Ngasa Dalam Meningkatkan Kerukunan Masyarakat: Studi Masyarakat Adat Jalawastu Brebes, Jawa Tengah - Sidik, Muhammad; Budiaman, Budiaman; Kurniawan, Nandi (Edukasi IPS, 2023)
This study aims to determine the meaning and role of the traditional ngasa tradition in increasing the unity of the Jalawastu community in Cisureh village, Keuntungan sub-district, Brebes Regency. The methodology used is qualitative. Data collection techniques were carried out by interviews, literature study and observation. The method used in data analysis is data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Ngasa Tradition by the Jalawastu Cultural Village Community has become a medium for the Jalawastu community and its surroundings in order to increase the harmony that has been formed for a long time. The form of the Ngasa Traditional Tradition by the Jalawastu people has now undergone changes and innovations, but the values ​​and meanings that are maintained by the community have not changed. The Ngasa tradition is still interpreted as an expression of gratitude to God for the crops and asking for blessings for the following year. In this Ngasa Tradition it prohibits the meaning of kinship, mutual cooperation, and cooperation between the Jalawastu people that have existed from the past to the present.